2016
DOI: 10.26419/res.00138.001
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregiving and Out-of-Pocket Costs: 2016 Report

Abstract: 20% off Sunday through Thursday and 10% off Friday and Saturday, plus a $10-per-day physical damage waiver. Visit website for full offer details. 5% off leisure daily, weekly, weekend, and monthly base rates, plus a free upgrade on compact through full-size car class bookings. * * Subject to availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…One national study found that 78% of family caregivers incurred expenses as a result of caregiving, spending an average of about $7000 on out‐of‐pocket costs in 2016. To cover caregiving expenses, family caregivers reported tapping into personal savings (30%), reducing retirement savings contributions (16%), or dipping into existing retirement savings (11%) …”
Section: Caregiving's Impact On Employment and Financial Well‐beingmentioning
confidence: 99%
See 1 more Smart Citation
“…One national study found that 78% of family caregivers incurred expenses as a result of caregiving, spending an average of about $7000 on out‐of‐pocket costs in 2016. To cover caregiving expenses, family caregivers reported tapping into personal savings (30%), reducing retirement savings contributions (16%), or dipping into existing retirement savings (11%) …”
Section: Caregiving's Impact On Employment and Financial Well‐beingmentioning
confidence: 99%
“…To cover caregiving expenses, family caregivers reported tapping into personal savings (30%), reducing retirement savings contributions (16%), or dipping into existing retirement savings (11%). 16…”
Section: Caregiving's Impact On Employment and Financial Well-beingmentioning
confidence: 99%
“…[4][5][6][7][8] Often, family members will fill the role of caregiver to support older adults in their own homes, which results in stress, burden, and financial issues. [9][10][11] Interventions are needed to support the needs of this vulnerable population and their caregivers in their homes. Voice-controlled intelligent personal assistants (VIPAs; eg, Amazon Echo and Google Home) may be one type of artificial intelligence technology that may improve the lives of older adults in the home setting.…”
mentioning
confidence: 99%
“…Caregiving also has significant financial impact on the caregiver. In the United States, 78% of caregivers incur out‐of‐pocket expenses averaging US$6954 annually . This burden falls disproportionately on the poor, people in rural areas, and ethnic minorities.…”
mentioning
confidence: 99%
“…This burden falls disproportionately on the poor, people in rural areas, and ethnic minorities. Work‐related stress is also common for employed caregivers …”
mentioning
confidence: 99%